"We had to run away": The Lovára's departure from the Protectorate of Bohemia and Moravia to Slovakia in 1939. Issue 1 (1st June 2022) - Hajská, Markéta
Abstract : This article focuses on the departure of the Lovára from the Protectorate of Bohemia and Moravia to Slovakia upon Czechoslovakia's disintegration in 1939. Based on a combination of archival research and oral history methods, it shows the Lovára's departure in the context of the contemporaneous measures and efforts of the state administration to limit the mobility of "nomadic Gypsies" in the Czech lands, continuous throughout the pre-war period, and to stoke anti-Gypsy sentiments which were politically supported and growing in the society of the time. This description is enriched by the perspectives of participants – narrations of Roms who were perceived as "nomads" and witnessed these events. The study opens epistemic dilemmas of how to determine the category of Lovára in the available archival sources as well as how to speak about the Lovára in a historical context without essentializing this category. The author reconstructs the presence of the Lovára's stay in the Czech lands during the First Republic from gendarme reports and other state administration documents and submits evidence of mobility of the Lovára in Czechia in the interwar decades. Their presence terminated upon Czechoslovakia's disintegration in 1939 when the Lovára and other Roms of Slovak home affiliation had to relocate themselves from the protectorate to Slovakia. The author analyses the circumstances and the course of the departure of Lovára and other Romani families from the Czech lands to Slovakia on the eve of the Second World War and presents the narrators' reflections on the sudden departure and subsequent peripeteia of individual families in Slovakia during the war.